Future climate change hotspots - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
A new study by the CGIAR Climate Program has matched future climate change “hotspots† with regions already suffering chronic food problems to identify highly-vulnerable populations, chiefly in Africa and South Asia, but potentially in China and Latin America as well, where in fewer than 40 years, the prospect of shorter, hotter or drier growing seasons could imperil hundreds of millions of already-impoverished people.